The Kitty Hawk Venture A Novel About Continuous Testing in DevOps to Support Continuous Delivery and Business Success - Scheaffer, Jeffrey (Apress, 2018)
An airline is supposed to make the experience of booking a flight easy, trouble free, and reliable. But when scheduling software breaks down and flights get canceled, customers will walk, and heads will roll. That's what Leigh Freemark faces the day she and her team launch a software upgrade that fails spectacularly and hits the media immediately. As Senior Director of Quality Assurance, her job is to make sure that code is market ready. And she's the one who must face the music when it doesn't. Tasked by senior management to find and fix the source of the failure, Leigh discovers just how essential it has become to radically improve the process of software development by introducing a concept called continuous testing. She must quickly learn what it means, how it works, and how to build it into her company's legacy system. But she soon discovers that managing change is much more difficult than it first appears. The airline business is changing fast, yet old traditions and loyalties still dominate. As she fights to convince her team to change or perish, she discovers that obstructions and opportunities come in surprising forms. *** In The Kitty Hawk Venture, the authors deliver a sound lesson in the importance of continuous testing while taking the reader inside the world of commercial aviation. Each chapter delivers distinct and vital learning opportunities wrapped inside a fast-moving narrative complete with interesting characters, intriguing situations, and even some humor. The book concludes with a "Flight Plan for Continuous Testing" that stands on its own as a valuable resource guide for digital leaders in their continuous testing journey. The story is immediately relatable to anyone who has worked in software development or for the companies that rely on it.